Indigofera tinctoria L. leaf powder promotes initiation of indigo reduction by inducing of rapid transition of the microbial community - Lopes, Helena de Fátima Silva; Tu, Zhihao; Sumi, Hisako; Yumoto, Isao (Frontiers in Microbiology, 2022)
Water-insoluble indigo is solubilized by the reducing action of microorganisms which occurs during fermentation. In natural indigo fermentation, composted leaves of Polygonum tinctorium L. (sukumo) is the raw material that has been used as both the indigo source and the bacterial inoculum. Ideally, indigo reduction occurs shortly after preparation of the fermentation vat. The time-to-reduction depends on the quality of the sukumo and the methods for preparation and management of the fermentation batch. We estimated of the effect of adding Indigofera tinctoria L. leaf powder (LP) to indigo fermentation in two fermentations originally exhibiting either rapid or slow time-to-reduction (T-sukumo and D-sukumo, respectively). Alkalihalobacillus spp. (97.7–98.4% similarities with Alkalihalobacillus macyae) were observed only in the LP-added T-sukumo fermentation liquor. They appeared from day 1 (0.7%) and increased to 24.4% on day 6, and their presence was related to indigo reduction. Differences in functional ratio between LP-added and its control batches revealed enhancement of pathways related to reconstitution of cellular functions and substrate metabolisms, to all of which Alkalihalobacillus spp. contributed intensively. In D-sukumo batch, appearance of bacteria necessary to initiate indigo reduction (principally Anaerobacillus/Polygonibacillus) was comparatively slower. LP promote earlier indigo reduction in both T- and D- sukumo based batches, owing to its promotion of microbiota transition. The effect of the LP was intensified from day 1 to day 2 in both sukumo using batches according to the assumed function of the microbiota. The initial effect of LP on the T-sukumo batches was more intense than that in the D-sukumo batches and was continued until day 3, while the duration in the T-sukumo batches was continued until day 5. Based on these observations, we propose that the LP functions through its phytochemicals that eliminate oxygen, stimulate the microbiota, and accelerate its transitional changes toward a suitable function that opens the pathway for the extracellular electron transfer using carbohydrates as a substrate.